Characteristics and Prevalence of Anterior Buccal Mandibular Depression Area in Cone Beam Computed Tomography Images - Köse Taha Emre (Sciendo, 2021)
Background/Aim: The purpose of this study was to assess the anterior buccal mandibular depressions (ABMD) prevalence and clinical characteristics at cone beam computed tomography images (CBCT).